Evaluasi Kualitas Layanan APEKESAH Versi 3 Menggunakan Metode e-Govqual dan Importance Perfromance Analysis (IPA) (Studi Kasus : Dinas Komunikasi Dan Informatika Kota Batam) - Dandy Eko Purwanto; Andi Reza Perdanakusuma; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
E-Government is the use of Information and Communication Technology (ICT) in the field of government. The policy of using e-Government is contained in the Instruction of the President of the Republic of Indonesia No. 3 of 2003 concerning national policies and strategies in the development of e-Government. The use of ICT in the government process (e-Government) itself will be able to increase the effectiveness, efficiency, transparency and accountability of governance. Batam City's Office of Communication and Information (Diskominfo) applies the concept of e-Government by building an online public complaints service called APEKESAH. Until now, there have been found several problems with services such as: (1) 43.75% of users experience problems with existing features in APEKESAH services; (2) 87.5% of users experienced problems on the appearance of the APEKESAH website, and (3) 62.5% of users experienced problems with service promises that were not met. To determine the quality of an e-Government service, a digital service quality evaluation model that is specific to the e-Govenrment domain called e-Govqual can be chosen and to measure the level of community satisfaction with performance and expectations of the community, the Importance Performance Analysis (IPA) method is used. . From the results of the study, there are 4 attributes of e-Govqual which are in the Science A Quadrant which states that there are 4 attributes that have high expectations but the performance is low. Therefore, a recommendation was made to correct these attributes so that the APEKESAH service is expected to meet the expectations of its users